PIK3CA-altered head and neck cancer- specific antitumor effect and underlying mechanism of nonsteroidal anti- inflammatory drugs - NGUYEN THI THANH NGA (The Graduate School, Ajou University, 2024)
Certain nonsteroidal anti-inflammatory drugs (NSAIDs) are well-known as not only Cyclooxygenase-2 (COX-2) inhibitors but also anti-tumor drugs for many types of cancer worldwide, including head and neck squamous cell carcinoma (HNSCC). It is claimed that mutated PIK3CA oncogenes are found in several human solid tumors. The oncogenic properties of PIK3CA, in particular, contribute to the development of human HNSCC. Some research shows that the anti-tumor effect of NSAIDs is more effective in PIK3CA-alternated HNSCCs, which highly express COX-2. However, the mechanisms have not been studied yet. In this study, we aimed to investigate some underlying mechanisms of Celecoxib and Sulindac Sulfide in PIK3CA-mutated HNSSC. FaDu and Detroit562 cell lines was used for wild-type and mutated PIK3CA models of HNSCCs, respectively. These two NSAIDs against tumor growth of the Detroit562 cell line by provoking endoplasmic reticulum (ER) stress and reactive oxygen species (ROS). Simultaneously, both Celecoxib and Sulindac Sulfide promote the expression of Death Receptor 5 (DR5), cleaved-caspase 3, and some mitochondria-related cell death markers such as BAX and BIM, and mitochondrial damage in altered-PIK3CA cells, resulting in significantly declined cell growth compared to the wild-type. Therefore, this study provides useful information to improve the efficiency of chemotherapy for PIK3CA-altered HNSCC patients. Keywords: Head and neck cancer; PIK3CA mutation; NSAIDs; ER stress; Reactive Oxygen Species; Mitochondrial dysfunction.
학위논문(석사)--의생명과학과,2024. 2
Keywords: ER stress; Head and neck cancer; Mitochondrial dysfunction.; NSAIDs; PIK3CA mutation; Reactive Oxygen Species